Differences in Principals' Data Use for Decision Making: An Administrative Probelm-Solving Perspective - Mingchu Luo; Jerry Will; Climetine Clayburn (The Advocate, 2013)
As school leaders, principals must seek, use, and make sense of data and information. This study presents the findings of a survey study of 182 high school principals’ data use and examines the differences in the extent of principals’ data use for decision making in solving various dimensions of administrative problems. Results show principals used data frequently for decision-making in instructional leadership, organization operational leadership and school vision leadership, among which data use in instructional leadership was most frequent. Principals’ use of data was significantly less frequent in the leadership dimension of collaborative partnerships and larger-context politics. This article ends with implications with regard to improving school leadership programs in meeting the emergent need of preparing data driven decision makers and suggestions for research relevant to the central topic of data-driven decision making.